La evangelización jesuítica en el Valle Calchaquí. Hacia la idealización de un nuevo hábitat jesuítico-calchaquí - Page, Carlos A. (Tempo da Ciência, 2000)
This paper tries to show the land use in a wide sector of northwestern Argentina inhabited by calchaquíes, at the time that break the Jesuits in the sector. They did so through their traditional flying missions, where the ethnic groups in the Valley took a stand against the advanced hesitant evangelizing, highlighting the particular reception with the children of Ignacio on their land. While the Indians reject the new religious ideas, ended up accepting the Jesuits as a refuge to avoid conflagrations with the conquerors. While the Jesuits, in a permissive attitude, they prioritized saving lives with a baptism which primarily defended from slavery or death. Amidst this context of religious spaces were occupied and lifting themselves to build a salvation which also include their souls, contradicted the prevailing system, so there were many alternatives. But the climate of greed and intolerance produced three major Hispanic fighting ended breaking progress with the creation of two incipient reductions. It was time when hope turned into tragedy.